Γ‐Secretase Inhibition Induces Muscle Hypertrophy in a Notch‐Independent Mechanism. Issue 3 (1st February 2018) - Rosa de Andrade, Ivone; Corrêa, Stephany; Fontenele, Marcio; de Oliveira Teixeira, John Douglas; Abdelhay, Eliana; Costa, Manoel Luis; Mermelstein, Claudia
Abstract: A wide variety of cellular processes and signaling events are regulated by the proteolytic enzyme γ‐secretase. Notch‐1 is one of the substrates of γ‐secretase and its role in the regulation of muscle differentiation has been well described. Importantly, besides Notch‐1, a number of proteins have been identified to undergo proteolysis by γ‐secretase. To date, the specific role of γ‐secretase during embryonic skeletal muscle differentiation has not been studied. Therefore, we address this question through the analysis of in vitro grown chick myogenic cells during the formation of multinucleated myotubes. The γ‐secretase inhibitor DAPT ( N‐N [‐(3, 5‐Difluorophenacetyl‐l ‐alanyl)]‐ S ‐328 phenylglycine‐ t ‐butyl‐ester) induces muscle hypertrophy. Knockdown of Notch‐1 using siRNA specific to chick shows no significant effect in myotube size, suggesting that γ‐secretase‐dependent effects on muscle hypertrophy in chick myogenic cells are Notch‐1‐independent. We also investigate the effects of γ‐secretase inhibition in the whole proteomic profile of chick myogenic cells. We identified 276 differentially expressed proteins from Label‐free proteomic approach. Data overview of interaction network obtained from STRING show that after γ‐secretase inhibition cells exhibited imbalance in protein metabolism, cytoskeleton/adhesion, and Sonic Hedgehog signaling. The collection of these results provides new insights into the role of γ‐secretase in skeletal muscle hypertrophy.